ANALISIS YURIDIS TERHADAP JUAL BELI AKUN DRIVER PADA LAYANAN TRANSPORTASI ONLINE DI KOTA KUPANG - Uly, Nila Wati L. J; Jacob, Yossie Maria Yulianty; Dju Bire, Chatryen M (Petitum Law Journal, 2025)
Technological advancements have driven the growth of the online transportation industry, which relies on virtual applications to facilitate services. However, misuse has emerged, such as the buying and selling of online driver accounts, particularly on the Maxim platform in Kupang City. This research is empirical, focusing on studying and analyzing data obtained from the research site. The aspects examined include the causes of the buying and selling of driver accounts in online transportation services in Kupang City and the legal consequences of such practices. The research findings indicate that: (1) The causes of the buying and selling of driver accounts in online transportation services in Kupang City include (a) Internal Causes: economic motivation, lack of legal awareness, and performance pressure. (b) External Causes: high market demand and intense competition among drivers. (2) The legal consequences of the buying and selling of driver accounts in online transportation services in Kupang City include permanent account blocking and blacklisting from Maxim's partner list. The researcher proposes the following recommendations: Maxim should review its bonus and incentive schemes for drivers, simplify the registration process for prospective driver partners with a faster, simpler, and more transparent procedure. Drivers should comply with application regulations and educate fellow drivers. Consumers should verify driver identities, remain cautious of fake accounts, and report suspicious accounts to the online transportation platform.